The Effect of Sales Promotion, Brand Image, and Online Customer Experience toward Repurchase Intention Mediated by Customer satisfaction - Steven Yong Hannes (iBuss Management, 2019)
This study is conducted to reveal the factors that are impacting Indonesian in repurchasing product and using service in Shopee Indonesia. It aims to know Sales Promotion, Brand Image, and Online Customer Experience are collectively and individual impacts repurchase intention in Indonesia.The data were gathered through simple random sampling with questionnaire. Then, the data were processed using Multiple Linear Regression Analysis. It is found that all factors collectively have a direct impact on repurchase intention. The result, Sales Promotion, Brand Image, and Online Customer Experience have significant impact on repurchase intention and customer satisfaction mediates the relationship between Sales Promotion, Brand Image, Online Customer Experience, and Repurchase Intention  Keyword:Repurchase Intention, Sales Promotion, Brand Image, Online Customer Experience, and Customer Satisfaction